2010
DOI: 10.1080/10871201003598785
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Hunter Support for Deer Herd Reduction as a Chronic Wasting Disease (CWD) Management Strategy

Abstract: The extent to which wildlife diseases like chronic wasting disease (CWD) are density dependent creates opportunities to manage them by implementing population reduction to disrupt disease spread and lower its prevalence. We tested a model to investigate the influence of risk perceptions and other salient beliefs on deer hunter support for deer density reduction as chronic wasting disease strategy in Wisconsin. We found that the influence of risk perceptions on hunter support for population goals was mediated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
(42 reference statements)
0
31
0
Order By: Relevance
“…As a result, most HD research on CWD has examined hunters': (a) participation in response to the disease and associated wildlife management actions, (b) perceptions of potential human health risks associated with CWD, and (c) concerns about impacts of the disease on wildlife (Brown et al, 2006;, Gigliotti, 2004Holsman & Petchenik, 2006;Holsman, Petchenik & Cooney, 2010;Lischka, Shelton, & Buhnerkempe, 2010;Miller, 2003Miller, , 2004Miller & Shelby, 2009;Needham, Vaske, Donnelly, & Manfredo, 2007;Needham, Vaske, & Manfredo, 2004Petchenik, 2006;Stafford, Needham, Vaske, & Petchenik, 2007;Vaske et al, 2004; Values, trust, knowledge, risk perception CO and WY big game guides and outfitters Anderies (2006) Behavioral intentions, satisfaction, information, communication, trust, knowledge NY general public and NY deer hunters Brown et al (2006) Concerns, behavior Black Hills SD deer hunters Gigliotti (2004) Attitudes, behavior WI hunters Heberlein and Stedman (2009) Holsman and Petchenik (2006) Behavior, risk perception, information Seven counties in Northern IL Miller (2003) Beliefs, behavior IL deer hunters Lischka, Shelton, and Buhnerkempe (2010) Miller (2004) Behavior, acceptability, risk perception Deer hunters in 8 states (AZ, CO NE, ND, SD, UT, WI, WY); elk hunters in 3 states (CO, UT, WY) Manfredo (2004, 2006) Vaske (2009a, 2009b) Deer hunters in 4 states (AZ, ND, SD, WI) Lyon and Vaske (2010) Vaske and Lyon (2010) WI hunters Cooney (2008) Cooney and Holsman …”
Section: Lesson 1: Hunters Vary In Their Behavioral Response To Cwdmentioning
confidence: 98%
See 2 more Smart Citations
“…As a result, most HD research on CWD has examined hunters': (a) participation in response to the disease and associated wildlife management actions, (b) perceptions of potential human health risks associated with CWD, and (c) concerns about impacts of the disease on wildlife (Brown et al, 2006;, Gigliotti, 2004Holsman & Petchenik, 2006;Holsman, Petchenik & Cooney, 2010;Lischka, Shelton, & Buhnerkempe, 2010;Miller, 2003Miller, , 2004Miller & Shelby, 2009;Needham, Vaske, Donnelly, & Manfredo, 2007;Needham, Vaske, & Manfredo, 2004Petchenik, 2006;Stafford, Needham, Vaske, & Petchenik, 2007;Vaske et al, 2004; Values, trust, knowledge, risk perception CO and WY big game guides and outfitters Anderies (2006) Behavioral intentions, satisfaction, information, communication, trust, knowledge NY general public and NY deer hunters Brown et al (2006) Concerns, behavior Black Hills SD deer hunters Gigliotti (2004) Attitudes, behavior WI hunters Heberlein and Stedman (2009) Holsman and Petchenik (2006) Behavior, risk perception, information Seven counties in Northern IL Miller (2003) Beliefs, behavior IL deer hunters Lischka, Shelton, and Buhnerkempe (2010) Miller (2004) Behavior, acceptability, risk perception Deer hunters in 8 states (AZ, CO NE, ND, SD, UT, WI, WY); elk hunters in 3 states (CO, UT, WY) Manfredo (2004, 2006) Vaske (2009a, 2009b) Deer hunters in 4 states (AZ, ND, SD, WI) Lyon and Vaske (2010) Vaske and Lyon (2010) WI hunters Cooney (2008) Cooney and Holsman …”
Section: Lesson 1: Hunters Vary In Their Behavioral Response To Cwdmentioning
confidence: 98%
“…Cooney (2008), for example, asked Wisconsin hunters to list what immediately comes to mind when they think about CWD. A content analysis of this open ended question revealed 12 different themes (e.g., disease is natural, no worries) and suggested that time and experience with CWD may have tempered some of initial concerns identified in other studies.…”
Section: Lesson 3: Perceived Human Health Risks Can Influence Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Heberlein and Stedman (2009), Cooney and Holsman (2010) and Holsman et al (2010) argue that initial attempts to control CWD in Wisconsin were less successful in reducing prevalence of the disease than they might have been with better engagement with hunters and non-hunting public in their planning and implementation. Wisconsin has a very large and densely concentrated deer population, which is known to be a factor in efficient disease transmission, and which could account for these relatively high numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Heberlein (2004) found that the Wisconsin strategy of treating CWD 'like a fire' had reduced the effectiveness of the management strategy of significant herd reduction in Wisconsin. Cooney and Holsman (2010) found that a government strategy of controlling the disease and reducing its spread might have had more support from hunters than the attempt to eradicate the disease. Holsman et al (2010) noted that although the majority of hunters saw CWD as something important to manage, few hunters actually increased their harvest of animals in spite of various government incentives, suggesting that hunter behaviour is unlikely to be an effective deer herd reduction management tool: "our findings call into question the efficacy of recreational hunting as a disease management tool when managers are seeking severe reductions in wildlife densities" (Other studies on hunter attitudes and behaviour involving the risks of CWD include: Gigliotti, 2004;Heberlein and Stedman, 2009;Holsman and Petchenik, 2006;Lyon and Vaske, 2010;Miller, 2003Miller, , 2004Miller and Shelby, 2009;Needham and Vaske, 2008;Vaske et al, 2006aVaske et al, , 2006b).…”
Section: Studies Of Behavioural and Attitudinal Factorsmentioning
confidence: 99%